2003
DOI: 10.1016/j.arthro.2003.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the thickness and curvature of articular cartilage of the femoral condyle

Abstract: When the chondral lesion is assumed at the weight bearing area of the medial or lateral femoral condyle, the anterior portion of the sulcus terminalis (the groove for meniscus) in the middle section of the lateral condyle is considered to be the optimal donor site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 14 publications
2
46
1
Order By: Relevance
“…Therefore, the sheep model appears to mirror the results we obtained in the present clinical study, in that incongruities ranging from flush to countersinking of less than 1 mm can be tolerated for autografting. Terukina reported that the average thickness of the cartilage in cadaver knee joints was 1.69 mm (range, 0.22-3.65 mm) [22]. If countersinking of an articular cartilage graft is less than 1 mm, then remodeling may be expected to occur because the graft plug and its surrounding tissue will be in contact with each other in the human knee joint.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the sheep model appears to mirror the results we obtained in the present clinical study, in that incongruities ranging from flush to countersinking of less than 1 mm can be tolerated for autografting. Terukina reported that the average thickness of the cartilage in cadaver knee joints was 1.69 mm (range, 0.22-3.65 mm) [22]. If countersinking of an articular cartilage graft is less than 1 mm, then remodeling may be expected to occur because the graft plug and its surrounding tissue will be in contact with each other in the human knee joint.…”
Section: Discussionmentioning
confidence: 99%
“…20,26 The variation in thickness of articular cartilage from the human knee has been mapped using cadaver tissue 27 and by arthrography. 28 The high loads transmitted through the patellofemoral joint and the resulting thick retropatellar articular cartilage support the theory that cartilage is modelled in response to mechanical load.…”
Section: Discussionmentioning
confidence: 99%
“…To harvest the grafts in arthroscopic procedure, peripheral parts of medial femoral condyle must be the first choice of donor site ( Fig. 1) because filling the joint with fluid in arthroscopic procedure, causes the lateral movement of patella [12,13]. In the graft harvesting step, introducing the tubular chisel perpendicular to the donor site is important.…”
Section: Surgical Technique and Postoperative Rehabilitationmentioning
confidence: 99%